Berendoi - Natashah Md. Nor; Rusli Harun; Fauzi Daud (Malaysia : UAS Communications (M), 1997)
Preparing and celebrating the ceremony of berendoi in Kedah, that means celebrating welcoming party to a newborn baby
Executive producer, Najib Shafion, Zabidi Sanip ; script, Ahmad Muhaimin
Narrator: Reemy Abdul Rahman
Keywords: Cradles